Population differences in the effect of context on personality in an invasive lizard. (17th September 2021) - Brand, Jack A; Naimo, Annalise C; Michelangeli, Marcus; Martin, Jake M; Sih, Andrew; Wong, Bob B M; Chapple, David G
Abstract: Within populations, individuals often differ consistently in their average level of behavior (i.e., animal personality), as well as their response to environmental change (i.e., behavioral plasticity). Thus, changes in environmental conditions might be expected to mediate the structure of animal personality traits. However, it is currently not well understood how personality traits change in response to environmental conditions, and whether this effect is consistent across multiple populations within the same species. Accordingly, we investigated variation in personality traits across two ecological contexts in the invasive delicate skink ( Lampropholis delicata ). Specifically, lizards from three different populations were repeatedly measured for individual activity in group behavioral assays under differing levels of food availability. We found that environmental context had a clear effect on the structure of lizard personality, where activity rates were not repeatable in the absence of food, but were repeatable in the presence of food resources. The difference in repeatability of activity rates across contexts appeared to be largely driven by an increase in among-individual variance when tested in the presence of food resources. However, this was only true for one of the populations tested, with food context having no effect on the expression of personality traits in the other two populations. Our results highlight the important role of environmental context in mediating the structure of animal personality traits and suggest that this effect may vary among populations. Abstract : Animals often show repeatable, among-individual differences in their behaviour (i.e., personality). However, how this variation changes across differing environmental contexts is not clear. We investigated how the presence of food resources altered behavioural variation in an invasive lizard. We found that activity rates were only repeatable in the presence, but not absence, of food resources. However, this effect varied among populations. These results suggest that environmental context can alter the structure of animal personality traits.